Presenting the Organizational Legitimacy Model in Iraqi Public Universities - Al Shuwaili, Ahmed Jalil Mohaisen; Bahrami, Hamid Reza; Shlaka , Tariq Kadhim; Aghaei, Enayat Ollah; Sadeghi, Mehrdad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: This study aimed to develop and validate a comprehensive model of organizational legitimacy in Iraqi public universities.Methodology: The research employed a quantitative–descriptive design. The statistical population consisted of 6,000 employees from Iraqi public universities, from which a sample of 361 participants was selected through stratified random sampling using Cochran’s formula. Data were collected using a researcher-developed questionnaire containing 80 items across 14 dimensions, including independence, innovation, organizational culture, participation, commitment, adaptability, leadership style, organizational support, reward systems, result orientation, mission clarity, organizational behavior, identity, and organizational structure. Validity was established through content and construct validity procedures, while reliability was confirmed with a Cronbach’s alpha coefficient of 0.86. Data analysis was performed using structural equation modeling (SEM) with LISREL software, and model fit was assessed using multiple fit indices.Findings: All dimensions demonstrated statistically significant path coefficients, generally exceeding 0.5, with many approaching or surpassing 0.8, indicating strong contributions to organizational legitimacy. The highest factor loadings were observed for independence, innovation, and organizational culture. All t-values exceeded 1.96, confirming statistical significance. Model fit indices indicated strong alignment with the observed data.Conclusion: The validated model confirms that organizational legitimacy in Iraqi public universities is a multidimensional construct influenced by both internal capabilities and external stakeholder perceptions. Strengthening independence, fostering innovation, cultivating organizational culture, promoting participation, and ensuring transparent governance are key strategies for enhancing legitimacy. The model offers a practical framework for policymakers and university leaders to guide institutional development and strategic planning in higher education.